2015
DOI: 10.1002/oa.2464
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Potential of Deciduous Incisor Wear as an Indicator of Weaning Using a Human Skeletal Population

Abstract: The aim of this work is to investigate the potential of wear on the earliest erupting teeth, the deciduous central incisors, for studying weaning in human skeletal populations. The study group is from mediaeval Wharram Percy, where existing δ 15 N data indicate cessation of breastfeeding occurred by about 24 months postpartum. The hypothesis tested is that there should be an increase in dental wear as breast milk is replaced with solid foods during weaning. Incisor wear is monitored using crown heights, measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
1
7
0
2
Order By: Relevance
“…These first signs of wear can be caused by weaning foods and implements used while the child is teething (Prowse et al, ). Elsewhere, signs of dental wear have been reported in individuals as young as 12–18 months (Mays, ; Prowse et al, ), and in this sample, dental wear was visible as early as 17 months. When using Middenbeemster as a reference sample, the recommended use is the quadratic equation with 68% PIs due to a higher calculated accuracy than for the linear and MARS models.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…These first signs of wear can be caused by weaning foods and implements used while the child is teething (Prowse et al, ). Elsewhere, signs of dental wear have been reported in individuals as young as 12–18 months (Mays, ; Prowse et al, ), and in this sample, dental wear was visible as early as 17 months. When using Middenbeemster as a reference sample, the recommended use is the quadratic equation with 68% PIs due to a higher calculated accuracy than for the linear and MARS models.…”
Section: Discussionsupporting
confidence: 56%
“…In populations with somewhat homogeneous diets, both the deciduous (i.e., baby or milk) and permanent (i.e., adult) teeth are subject to a fairly constant rate of wear, providing the framework for various methods of age-atdeath estimation for adults (Brothwell, 1972;Faillace, Bethard, & Marks, 2017;Kim, Kho, & Lee, 2000;Kvaal, Kolltveit, Thomsen, & Solheim, 1995;Lovejoy, 1985;Maat, 2001;Mays, 2002;Mays, de la Rua, & Molleson, 1995); however, this concept has yet to be applied to nonadults. Previous studies employing deciduous dental wear have noted a strong correlation between the observed wear and age but were mainly focused on dietary transitions related to weaning and potential dietary differences in social status (Dawson & Brown, 2013;Mahoney et al, 2016;Mays, 2016;Mays & Pett, 2014;Prowse et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Prowse et al () recorded wear in 79% of teeth in their sample, and the youngest individual with wear was 1.5 years of age. Similarly, Mays () observed wear in a sample of deciduous teeth from the mediaeval site of Wharram Percy as early as 18 months for the mandibular incisors and 18–24 months for the maxillary incisors.…”
Section: Discussionmentioning
confidence: 87%
“…Estas diferencias significativas respecto al resto son interesantes ya que estos dos individuos tienen una edad cercana al período de introducción y consolidación tanto de comidas complementarias como papillas o semilíquidos (Sellen y Smay, 2001;Halcrow y Tayles, 2008;Meehan et al 2013;Mays, 2016;Mays et al 2017;Ventresca-Miller et al 2017;Scott y Halcrow, 2017), como de alimentos más propios de la dieta adulta.…”
Section: Discussionunclassified